1995
DOI: 10.1136/jnnp.58.6.699
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary cerebral haemorrhage with amyloidosis, Dutch type (HCHWA-D): clinicopathological studies.

Abstract: Clinical and neuropathological findings are reported in 63 patients with hereditary cerebral haemorrhage with amyloid angiopathy. Patients hadf mostly recurrent strokes, and at least 80% of these were haemorrhages. Almost a third ofthe patients died within a year of their first and only recorded haemorrhage, half of them within two weeks. This angiopathy was restricted to the cerebral and cerebeliar cortex and its covering leptomeninges. As the most important consequence, haemorrhagic infarcts and haemorrhages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 21 publications
3
97
0
Order By: Relevance
“…These findings suggest that chronic activation of plasminogen can undermine HCSM cell attachment by degradation of cell adhesion components. DISCUSSION CAA is a common pathological feature of most patients with Alzheimer's disease and is prominently found in several rare hereditary cerebrovascular amyloidosis disorders involving mutations within A␤ (1,16,19). The reasons for the accumulation of A␤ in cerebral blood vessels remain unresolved although recent studies (47,48) suggest that it may involve the flow of parenchymal A␤ through interstitial fluid drainage pathways and ineffective transport into the circulation.…”
Section: Pathogenic A␤ Stimulates the Expression And Cell Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that chronic activation of plasminogen can undermine HCSM cell attachment by degradation of cell adhesion components. DISCUSSION CAA is a common pathological feature of most patients with Alzheimer's disease and is prominently found in several rare hereditary cerebrovascular amyloidosis disorders involving mutations within A␤ (1,16,19). The reasons for the accumulation of A␤ in cerebral blood vessels remain unresolved although recent studies (47,48) suggest that it may involve the flow of parenchymal A␤ through interstitial fluid drainage pathways and ineffective transport into the circulation.…”
Section: Pathogenic A␤ Stimulates the Expression And Cell Surfacementioning
confidence: 99%
“…The reasons for the accumulation of A␤ in cerebral blood vessels remain unresolved although recent studies (47,48) suggest that it may involve the flow of parenchymal A␤ through interstitial fluid drainage pathways and ineffective transport into the circulation. A profound deleterious consequence of CAA, particularly in the hereditary forms, is cerebral hemorrhage that can result in serious debilitation or death (19,49,50). Although the mechanisms responsible for the development of hemorrhage in CAA are unclear proteolytic activities may contribute to this pathologic event.…”
Section: Pathogenic A␤ Stimulates the Expression And Cell Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…These degenerating smooth muscle cells have been implicated in the overproduction of A␤PP and A␤ in the cerebral vessel wall further suggesting the active involvement of these cells in the progression of this cerebrovascular pathology (17)(18)(19). Similar to these in vivo observations, we have reported that A␤- , the more pathogenic form of the wild-type peptide, causes severe cellular degeneration accompanied by a marked increase in the level of cell-associated A␤PP in cultured human cerebrovascular smooth muscle (HCSM) cells (20 -22).…”
Section: Fibrillar Amyloid-␤ Protein (A␤)mentioning
confidence: 99%
“…HCHWA-D patients suffer from hemorrhagic strokes, infarcts, and vascular dementia (Wattendorff et al, 1995). Life expectancy is reduced: the first stroke occurs between the ages of 40 and 65 and is fatal in two thirds of the patients (Wattendorff et al, 1982;.…”
Section: Introductionmentioning
confidence: 99%